The Relationship among Iranian EFL Teachers’ Professional Identity, Self-Efficacy and Critical Thinking Skills - Negar Moslemi; Parya Habibi (HOW)
Teachers’ beliefs, attitudes, and identities have been considered as the main factors in improving their performance to enhance students’ learning. The present study aimed to explore the relationship among Iranian EFL teachers’ professional identity, their self-efficacy, and their critical thinking skills in their teaching process. To achieve the objective of the study, 75 EFL teachers participated in this study. Three instruments were used to collect the required data including professional identity, TEBS-Self questionnaires, and the Watson‐Glaser Critical Thinking Appraisal test. The findings in the present study demonstrate that there was a strong positive relationship of the EFL teachers’ professional identity between their self-efficacy and their critical thinking skills. The results of the ANOVA (analysis of variance models) test indicated that the EFL teachers’ professional identity could predict their self-efficacy and their critical thinking skills.